Development of Automated Environmental Control System for Portable Greenway Section - Kyrpota, F. (ХНУРЕ, 2023)
In this paper, issues of green living were considered, and as result, its advantages in future agriculture were identified. In course of analysis, different types of au tomatic greenhouses were compared, in particular their main parameters, which are most often taken into account when choosing greenhouse.
Keywords: automated greenhouse; green circulation